Application of Animated Video Media to Understanding Bullying Behavior at MTsN 2 Aceh - Fakhriza, Atika; Khaira, Wanty (Pusdikra Publishing, 2025)
This study aims to test the effectiveness of classical services based on animated video media in improving students' understanding of bullying behavior at MTsN 2 Aceh Besar. Using a quantitative approach with a pre-experimental one group pre-test and post-test design, the research sample consisted of 32 students in grades VII-4 selected through purposive sampling techniques based on the results of the bullying behavior questionnaire. The research instrument was a bullying behavior questionnaire that had been tested for validity and reliability. The results of data analysis showed that the average score of students' understanding decreased from 89.18 in the pre-test to 71.84 in the post-test. This decrease was interpreted as an increase in students' awareness of the forms and impacts of bullying. The paired sample t-test showed a significance value of 0.003 (<0.05), which indicated a significant difference between the scores before and after the intervention. These findings prove that classical services based on animated video media are effective in improving students' understanding of bullying behavior, including verbal, physical, and relational aspects.